Clonal diversity and spatial dissemination of multi-antibiotics resistant Staphylococcus aureus pathotypes in Southwest Nigeria - Akinduti, Akinniyi Paul (PLoS One, 2021)
Spread of genetically diverse Staphylococcus aureus characterized with multi-antibiotic resistance and regulated by high level agr functionalities in several communities in southwest Nigeria was investigated and evaluated for infection control. Staphylococcus aureus pathotypes recovered from 256 cases including purulent pus from skin infections, soft tissue aspirates, wounds, otorrhea, eye, throat and endocervical infections were assayed for biofilm and antibiogram. Further genotyped with micro-array, mapped for geospatial distribution and evaluated for clonal diversity and functional accessory gene regulators (agr). Significant Staphylococci infection among the ages (OR:0.021, CI:0.545–1.914) and female gender with prevalence rate of MSSA (53.0%) and MRSA (1.5%) (OR:1.021, CI:0.374–1.785) were observed. More than 52.5% resistance rates to tetracycline and amoxicillin with significant median resistance were observed in all the infection cases (p = 0.001). Resistance rate of 78.8% at MIC(50) 32μg/ml and MIC(90) 128μg/ml to amoxicillin-clavulanate, and more than 40% resistance to ceftazidime, ciprofloxacin and tetracycline of MIC(90) and MIC(50) at 32 μg/ml were observed. Strains with multi-antibiotic resistance index above 0.83, high beta-lactamase and strong biofilm clustered into separate phylo-group. Heterogeneous t442 (wound and pus), t657 (wound), t091 (ear) and t657 (ear and wound) revealed high phylogenetic diversity. Only 4.6% pvl+ MSSA-CC1 agrI, pvl+ MSSA-CC5 (13.6%) and pvl+ MRSA-CC7 agrII (4.6%), expressed enterotoxin, leukocidins, proteases and resistance gene determinants. Livestock clonal types clustered with identified community-associated strains. Clonal dissemination of resistant pvl+ MSSA-CC1 and MRSA-CC5 encoding agr were predominant in several peri-urban communities where adequate geno-surveillance, population-target antimicrobial stewardship, extensive community structured infection control programs are needed to prevent further focal dissemination.